Facile and controllable synthesis of hydroxyapatite/graphene hybrid materials with enhanced sensing performance towards ammonia1. Issue 15 (7th August 2015) - Zhang, Qing; Liu, Yong; Zhang, Ying; Li, Huixia; Tan, Yanni; Luo, Lanlan; Duan, Junhao; Li, Kaiyang; Banks, Craig E.
<x xml:space="preserve">Abstract</x> Hydroxyapatite/graphene hybrid materials with two different morphologies exhibit high sensing ability towards ammonia at room temperature.